A Ukrainian Student Visit at an Austrian School in Times of War: Implications for Peace Education - Bacher, Sabrina; Bacher, Marina; Kraler, Christian; Binytska, Kateryna (The Modern Higher Education Review, 2024)
This paper explores the impact of short-term international educational exchange programs amidst conflict. It builds on the premise that intercultural interactions are crucial for developing and cultivating mutual understanding, respect, collaboration, and peace. More specifically, the manuscript focuses on a specific case study where Ukrainian students visited an Austrian school amidst ongoing conflict. It examines the program through the lens of both Ukrainian and Austrian students. Methodologically, we collected empirical data through questionnaires which contained both open-ended and closed-ended questions. The qualitative data was analysed through triangulated coding with three coders, deriving the main and subcategories inductively. The findings highlight significant benefits for Ukrainian students through cultural immersion and interactions with Austrian peers. Despite challenges such as language barriers, the short-term exchange contributed to broadening perspectives and nurtured intercultural competencies. The study underscores the importance of structured planning, language support, and inclusive activities in optimizing educational exchange programs to promote mutual understanding in multicultural settings with the overall aim of contributing to a more peaceful coexistence of humanity, which is the primary goal of peace education. Finally, the paper suggests avenues for developing future initiatives to enhance peace education through cross-cultural learning.